2006
DOI: 10.1007/s00431-006-0223-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of non-responsiveness to standard high-dose gamma-globulin therapy in patients with acute Kawasaki disease before starting initial treatment

Abstract: Clinical, laboratory, and echocardiographic data were retrospectively analyzed in 112 patients with acute Kawasaki disease who received high-dose (2 g/kg) intravenous gamma-globulin (IVIG) treatment within 2 days and were compared for those who were responsive and non-responsive to initial IVIG treatment. Coronary arteries adjusted for body surface area (BSA) were evaluated quantitatively by comparison with the mean dimensions for 85 normal control subjects. The incidence of coronary abnormalities was higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
309
4
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(341 citation statements)
references
References 29 publications
18
309
4
10
Order By: Relevance
“…Kawasaki disease children who are resistant or refractory to initial immunoglobulin therapy with recrudescence of fever are thought to be a ''hyperinflammatory phenotype'' and are considered to be at a higher risk for coronary artery aneurysms 3,[16][17][18][19] and other complications. 20,21 Several factors have been reported to be associated with refractory cases, including younger age, 22 male gender, 23 earlier presentation, 3 initial treatment before day 4 of fever, lower platelets, 3,22 lower hemoglobin, 3,24 higher white blood cell 25 and bands counts, 3 elevated C-reactive protein 3,19,22,24,26,27 and erythrocyte sedimentation rate, 18 elevated lactate dehydrogenase, 19,24 abnormal liver function, 3,19,22,23,26,27 lower serum albumin 23,28,29 and certain biomarkers, 30-33 among others.…”
Section: Discussionmentioning
confidence: 99%
“…Kawasaki disease children who are resistant or refractory to initial immunoglobulin therapy with recrudescence of fever are thought to be a ''hyperinflammatory phenotype'' and are considered to be at a higher risk for coronary artery aneurysms 3,[16][17][18][19] and other complications. 20,21 Several factors have been reported to be associated with refractory cases, including younger age, 22 male gender, 23 earlier presentation, 3 initial treatment before day 4 of fever, lower platelets, 3,22 lower hemoglobin, 3,24 higher white blood cell 25 and bands counts, 3 elevated C-reactive protein 3,19,22,24,26,27 and erythrocyte sedimentation rate, 18 elevated lactate dehydrogenase, 19,24 abnormal liver function, 3,19,22,23,26,27 lower serum albumin 23,28,29 and certain biomarkers, 30-33 among others.…”
Section: Discussionmentioning
confidence: 99%
“…Egami et al showed that resistance to IVIG treatment can be predicted evaluating age, illness days, platelet count, serum transaminase level and CRP [13]. A multivariate analysis by Sano et al in 112 patients with KS, who received IVIG within 2 days, selected high CRP, total bilirubin and aspartate aminotransferase as independent predictors of low rate of response to initial IVIG treatment, finding that patients with at least two increased predictors of the three might result unresponsive to IVIG [14]. Failure of a single IVIG dose might occur in up to 11.6% of KS patients, especially if displaying low hemoglobin, high neutrophil count and low albumin [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Sano T, patients who were non-responsive to intravenous immunoglobu- lin (IVIG) had higher CRP and aspartate aminotransferase (AST). Total bilirubin and Body surface area adjusted coronary dimensions were statistically more in diameter in non-responsive group (25). Kubayashi et al proved that sodium ≤ 133 mM/L, neutrophils > 80%, days of illness at initial treatment ≤ four days, AST, age in months ≤ two, platelet count < 300,000/µL and CRP ≥ 10 mg/dL were independent predictors of non-responsive-IVIG, but not for coronary complications (26).…”
Section: Discussionmentioning
confidence: 99%
“…Kubayashi et al proved that sodium ≤ 133 mM/L, neutrophils > 80%, days of illness at initial treatment ≤ four days, AST, age in months ≤ two, platelet count < 300,000/µL and CRP ≥ 10 mg/dL were independent predictors of non-responsive-IVIG, but not for coronary complications (26). The retrospective study which looked at risk factors for refractory KD in Japan resulted that in 20% of cases who did not respond to initial IVIG therapy, risk factors associated with the need for retreatment were initial treatment on/before the fifth day of illness, recurrent episodes of KD and male gender) (25). A scoring system by Nakano H. et al used age, CRP and platelet count to predict and determine the patients with higher chance for coronary problems (27).…”
Section: Discussionmentioning
confidence: 99%